Electrosurgical smoke: a real concern. - Chowdhury, KK; Meftahuzzaman, SM; Rickta, D; Chowdhury, TK; Chowdhury, BB; Ireen, ST (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Jul;20(3):507-512 The abstract of this article is available on the PubMed website